IMPLEMENTATION OF HUMAN RESOURCE MANAGEMENT STRATEGIES IN NATIONAL COMPANIES IN THE ERA OF DIGITAL TRANSFORMATION IN INDONESIA - Khaeruman, Khaeruman; Dewi, Irma Nurmala; Ahmed, Abdal (International Journal of Multidisciplinary Research and Literature, 2025)
The objective of this investigation is to evaluate the effectiveness of human resource management (HRM) strategies in Indonesian national companies as they navigate the digital transformation era. The qualitative case study approach was implemented in three national companies operating in the banking, manufacturing, and telecommunications sectors. Data were gathered via in-depth interviews, observation, and documentation, and subsequently analyzed using NVivo 12 software. The findings indicate that HRM management strategies focus on three primary components: enhancing employee digital competencies through reskilling and upskilling programs, integrating technology into the HRM system, and reinforcing an organizational culture that is adaptable to digital change. The successful implementation of a digital HRM strategy is highly dependent on transformative leadership, digital literacy, and readiness for a new work culture. This study contributes theoretically to the advancement of strategic HRM theory and presents practical recommendations for national companies to enhance competitiveness via digital-based HRM